2010
DOI: 10.2174/156800910793605794
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin/LEF-1 Signaling in Chronic Lymphocytic Leukemia (CLL): A Target for Current and Potential Therapeutic Options

Abstract: There is a growing body of evidence that Wnt signaling, which is already known to play a critical role in various types of cancer, also has a vital function in B cell neoplasias, particularly in chronic lymphocytic leukemia (CLL). It is known that Wnt proteins are overexpressed in primary CLL cells and several physiological inhibitors are partly inactivated in this disease. Furthermore, β-catenin is upregulated upon Wnt stimulation and cooperates with the transcription factor lymphoid enhancer binding factor-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…In normal development Wnt activity is shortlived and expression of Wnt target genes oscillates, suggesting that Wnt activity is controlled by inherent negative feedback loops (8). Uncontrolled activation of the central effector of Wnt signaling, β-catenin, has been causatively linked to genome instability in multiple cancers, including hematopoietic malignancies (9)(10)(11)(12). However, how uncontrolled β-catenin promotes genomic instability in these malignancies is unknown.…”
mentioning
confidence: 99%
“…In normal development Wnt activity is shortlived and expression of Wnt target genes oscillates, suggesting that Wnt activity is controlled by inherent negative feedback loops (8). Uncontrolled activation of the central effector of Wnt signaling, β-catenin, has been causatively linked to genome instability in multiple cancers, including hematopoietic malignancies (9)(10)(11)(12). However, how uncontrolled β-catenin promotes genomic instability in these malignancies is unknown.…”
mentioning
confidence: 99%
“…42 Moreover, b-catenin, as well as LEF1/b-catenin inhibitors, prolonged CLL cell survival, indicating that the Wnt pathway could play a role in CLL pathogenesis. [40][41][42][43] Indeed, other genes belonging to this pathway were mutated in our discovery panel (PTPRU, MED12, and INVS) in a mutual exclusive fashion. [44][45][46] Notably, MED12 has been recently recognized as a driver in CLL by Landau et al, 47 and in this context, a pivotal role in CLL pathogenesis has been ascribed to the Wnt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…39 The role of the Wnt pathway in CLL has been explored in several papers. [40][41][42][43] Gene expression analysis showed that several members of the Wnt family, as well as the transcription factor LEF1, are overexpressed in CLL cells compared with peripheral blood B cells from healthy donors. 40,41 On the other hand, it was reported that Wnt/b-catenin inhibitor genes were hypermethilated.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Most of the studies reported that up-regulation of B-CATENIN causes the stimulation of WNT pathway and overexpressed WNT proteins contribute to the pathogenesis of hematologic malignancies like acute myeloid leukemia (AML), chronic lymphocytic leukemia (CLL) and T cell acute lymphoblastic leukemia. [3][4][5] APC gene is a multi-domain protein and inactivating mutations or methylations lead to deregulated WNT signaling which has been firstly implicated in colorectal tumor evolution. 6,7 APC gene is the negative regulator of the WNT pathway, has been methylated in solid tumors especially colon prostate, breast cancers, multiple myeloma and acute leukemia.…”
Section: Introductionmentioning
confidence: 99%